Tanggap Pertumbuhan dan Hasil Tomat (Lycopersicum esculentum Mill.) yang Diaplikasi Mineral Organik T-2 Karunia dan Pupuk Kandang Kambing - Tony Willem Duwiri; Antonius Suparno; Baso Daeng (Agrotek, 2015)
This research aim to study the effect of organic mineral fertilizer dose level T-2 Gifts and goat manure on growth and yield of tomato. This research was conducted in the Green House Fapertek UNIPA Manokwari. This study used an experimental method and is designed using completely randomized design (CRD) berfaktor. The treatment consisted of five dose levels of organic mineral fertilizer T-2 Gifts and goat manure 2 dose levels. Interaction dosage of goat manure and organic mineral soil remediation doses of T-2 gift giving real influence on the observation variables days to flowering plants and heavy fruit crop harvest. Dose levels of organic mineral soil remediation T-2 gift giving real effect to all variables observation.